Information System Benefits Improvement Model, Information Quality Through User Satisfaction, Information Quality and Organization At Hospital X - Nurrohman Hardiansyah; Ratna Indrawati; Nofierni Nofierni (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Hospital Information System aims to provide accurate, timely, and relevant information to support management functions and decision-making in health services in hospitals. This study examines the influence of user satisfaction, information quality, and organizational support on the benefits obtained from SIRS, both directly and indirectly. The approach used in this study is quantitative with the explanatory causality method, and the analysis technique in this study uses Structural Equation Modeling (SEM). The respondents of the study were 198 professional care providers (PPA) who were directly involved in the use of SIRS at the Sultan Agung Islamic Hospital, Banjarbaru. The results of this study indicate that the factors of user satisfaction, information quality, and organizational support have a major influence on the benefits both directly and indirectly received from the use of this system, with a determination coefficient of 84.8%. This means that more than 80% of the benefits obtained by the hospital in using the hospital information system are determined by how satisfied the user is with the system used. This indicates a good relationship between the four factors in increasing the benefits of the hospital information system at RSI Sultan Agung Banjarbaru. Therefore, hospitals are advised not to only focus on developing one aspect, but also to maximize the four aspects in order to provide more optimal results.